Polityka zachodnia cesarzy Marcjana (450-457) i Leona I (457-474) - Pigoński, Łukasz, 1991- (Byzantina Lodziensia, 2019)
The subject of analysis of the above work is how the Eastern Roman Empire reacted to barbarian invasions and internal problems, that eventually brought demise to the Empire in the West. During these times the Eastern Roman Empire was ruled by two emperors - Marcian (450-457) and Leo I (457-474), who had completely different concepts on how to conduct the western policy. Based on the relations with the Vandal Kingdom in Africa, the Hun Empire and the Ostrogoths in the Balkans, the pragmatic and considerate policy of Marcian was confronted with ambitious plans of Leo to save the Western Roman Empire from the collapse. The reigns of Marcian and Leo provide a unique testimony on the attempts to face the challenges posed before the civilized world by the turbulent migration age.